Prosociality Inspired by the Charism of the Unity of Chiara Lubich. An Application in the School of Childhood - Robert Roche Olivar; Sandra Rodríguez Gil (Nicolaus Copernicus University in Toruń, 2019)
This article presents two distinct parts. The first tries to answer the questions: How do spiritual or religious intuitions apply in life? Or, better, how do certain evangelical passages come to pass when they pass through a structuring of a system of thought? What application characteristics can a certain charism have when analysed and experimentally applied from a scientific perspective and methodology? In this first part, we present a biographical and professional journey of an academic group that started from a concern and experience of a person, the first author, for about 38 years. This group was trying to develop a theoretical-application model initially originated in the educational field and currently active in various areas of human activity, responding to the spiritual charism of a contemporary woman recognised by an institution as universal by the church. The second part shows one of the last experiences of these applications in the educational field. This experience occurs specifically in the infantile age, which is a crucial stage to mark positive tracks in the development of the personality, as well as positive patterns for the later interpersonal and social relations that employ prosociality and cooperation with a very experimental methodology.